Pengaruh Pemberian Nutrisi Phaseolus radiatus L. Terhadap Tingkat Kepadatan Spermatozoa Mus musculus L. - Anastasia A Basir; Munif S Hassan; Theophillus Buranda; Eddyman W Ferial (Biogenesis: Jurnal Ilmiah Biologi, 2013)
Research about the effect of greenpeal sprout Phaseolus radiatus L. on the spermatozoa density of Mus musculus L. has been done. The purpose of this research was to know the effect of greenpeal sprout Phaseolus radiatus L. on the spermatozoa density of Mus musculus L. Mice is feeded with greenpeal sprout for 21 days. The sperm is collected from cauda of epididimis diluted physiological solution and counted using haemocytometer. The result showed that micefeeding with greenpeal sprout could increase the density of its spermatozoa. It showed from increase the density of its spermatozoa from 11,05 million/cc sperm in control group become 11,78 million/cc sperm in treatment group by use of T test. Fidelity guarantee 95 percent explain that there are positive correlation and significant. Keywords: Greenpeal sprout, Mus musculus L., Phaseolus radiatus L., Spermatozoa